2018
DOI: 10.1002/jsfa.8894
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of proanthocyanidins in leaves of Chamaecyparis obtusa var. formosana as strong α‐glucosidase inhibitors

Abstract: Proanthocyanidins in HWE were viewed as potential natural α-glucosidase inhibitors for decreasing postprandial hyperglycemia. The results indicated that specific structural characteristics of proanthocyanidins would be required for α-glucosidase-inhibitory activity. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…The IBPP fraction of the guarana powder has several oligomers bearing varying degrees of hydroxylation, thus providing different bond and interaction sites for the formation of the polyphenol-enzyme complex. Additionally, although afzelechin has never been identified in the SPP fraction of guarana powder, it was found to be present in the IBPP fraction and a recent study has shown a positive relationship between the proportion of dimers as well as the proportion of afzelechin extension units in proanthocyanidin fractions and their alpha-glucosidase inhibition capacity [71]. This difference between the SPP and IBPP composition may be an important factor for their effectiveness as alpha-glucosidase inhibitors.…”
Section: Insoluble-bound Phenolic Profilementioning
confidence: 98%
“…The IBPP fraction of the guarana powder has several oligomers bearing varying degrees of hydroxylation, thus providing different bond and interaction sites for the formation of the polyphenol-enzyme complex. Additionally, although afzelechin has never been identified in the SPP fraction of guarana powder, it was found to be present in the IBPP fraction and a recent study has shown a positive relationship between the proportion of dimers as well as the proportion of afzelechin extension units in proanthocyanidin fractions and their alpha-glucosidase inhibition capacity [71]. This difference between the SPP and IBPP composition may be an important factor for their effectiveness as alpha-glucosidase inhibitors.…”
Section: Insoluble-bound Phenolic Profilementioning
confidence: 98%
“… 30 CoLE contained flavonoids, flavonoid glycosides and proanthocyanidins. 13 , 14 It was assumed that the PTPase inhibitory activity of CoLE treatment in rats was contributed by flavonoids and proanthocyanidins. CoLE treatment has potential to improve both insulin and leptin resistance.…”
Section: Resultsmentioning
confidence: 99%
“… 13 Proanthocyanidins with A-type linkages derived from CoLE exhibited potent α-glucosidase inhibitory activity. 14 However, in vivo anti-diabetic activity of Cupressaceae leaf extract has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Effective α ‐glucosidase inhibitors can block the enzyme in the small intestine to decompose the dietary complex carbohydrates and lower the levels of postprandial blood glucose. α ‐Glucosidase inhibitors (AGIs) such as voglibose, acarbose, and miglitol are usually applied in clinical treatment of type‐2 diabetes by retarding carbohydrates hydrolysis and reducing blood glucose levels . However, those synthetic AGIs were reported to cause diarrhea and flatulence, and high IC 50 values also limits their use.…”
Section: Introductionmentioning
confidence: 99%
“…-Glucosidase inhibitors (AGIs) such as voglibose, acarbose, and miglitol are usually applied in clinical treatment of type-2 diabetes by retarding carbohydrates hydrolysis and reducing blood glucose levels. 5 However, those synthetic AGIs were reported to cause diarrhea and flatulence, 6,7 and high IC 50 values also limits their use. The search for efficient and safer AGIs from plant-based foods has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%